How do you solve for x in 2x^2+4x-1=0 using the quadratic formula?

1 Answer
Oct 9, 2017

Let's see.

Explanation:

Let the quadratic equation be ax^2 + bx + c= 0

Then the quatratic formula for solving x is rarr

x =( -b +-sqrt(b^2 -4ac))/(2a)

In the equation, 2x^2+4x-1=0, a=2,b=4,c=-1.

Now, substituting the values we get,
x =( -4 +-sqrt(4^2-4xx2xx(-1)))/(2*2)

:.x = (-4 +-sqrt(16 +8))/(4)

:.x = (-4 +-sqrt(24))/(4)

:.x = (-4 +-2sqrt(6))/(4)

So, we get two real solutions for x:

:.x=(sqrt(6)/2-1), x=-(sqrt(6)/2+1) (Answer)

Hope it Helps :)